2005
DOI: 10.1210/en.2004-1445
|View full text |Cite
|
Sign up to set email alerts
|

Increased Pituitary Vascular Endothelial Growth Factor-A in Dopaminergic D2 Receptor Knockout Female Mice

Abstract: Vascular endothelial growth factor (VEGF)-A is an important angiogenic cytokine in cancer and pathological angiogenesis and has been related to the antiangiogenic activity of dopamine in endothelial cells. We investigated VEGF expression, localization, and function in pituitary hyperplasia of dopamine D2 receptor (D2R)-knockout female mice. Pituitaries from knockout mice showed increased protein and mRNA VEGF-A expression when compared with wild-type mice. In wild-type mice, prolonged treatment with the D2R an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
58
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 47 publications
11
58
0
Order By: Relevance
“…All the six normal pituitaries expressed VEGF-A to a similar extent in 31-60% of all cells, confirming previous reports that not only FS cells (5-10% of all pituitary cells), but also endocrine cells produce VEGF-A ( Jabbour et al 1997, Fan & Iseki 1998, Cristina et al 2005. In pituitary adenomas, VEGF-A was not detectable in 5 out of 39 cases (13%), which is in agreement with a previous study in which 8% of the adenomas studied did not secrete VEGF-A in vitro (Lohrer et al 2001; Table 1).…”
Section: Vegf-a Expression In Normal and Adenomatous Human Pituitarysupporting
confidence: 88%
See 1 more Smart Citation
“…All the six normal pituitaries expressed VEGF-A to a similar extent in 31-60% of all cells, confirming previous reports that not only FS cells (5-10% of all pituitary cells), but also endocrine cells produce VEGF-A ( Jabbour et al 1997, Fan & Iseki 1998, Cristina et al 2005. In pituitary adenomas, VEGF-A was not detectable in 5 out of 39 cases (13%), which is in agreement with a previous study in which 8% of the adenomas studied did not secrete VEGF-A in vitro (Lohrer et al 2001; Table 1).…”
Section: Vegf-a Expression In Normal and Adenomatous Human Pituitarysupporting
confidence: 88%
“…In normal pituitary, both folliculostellate (FS) cells and endocrine cells were identified as sources of VEGF (Gospodarowicz et al 1989, Jabbour et al 1997, Fan & Iseki 1998, Gloddek et al 1999, Renner et al 2002, Cristina et al 2005, Nakakura et al 2006. In human pituitary adenomas, tumour cells synthesize and release VEGF-A (Lloyd et al 1999, Iuchi et al 2000, Lohrer et al 2001, McCabe et al 2002, Fukui et al 2003, Viacava et al 2003, Onofri et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is strongly correlated to angiogenesis (Lu et al, 2008;Ristori et al, 2008). The anti-mitotic action of D2 receptors on endothelial cells (Basu et al, 2001;Cristina et al, 2005) may explain the potentiating effect of low-dose eticlopride on L-DOPAinduced angiogenesis in this study. High-dose eticlopride did not, however, produce a more marked potentiation.…”
Section: Discussionsupporting
confidence: 54%
“…Indeed, DA inhibits endothelial proliferation and vessel growth through activation of D2 receptors (Basu et al, 2001;Cristina et al, 2005;Gomez et al, 2006;Sarkar et al, 2004). By contrast, in vitro and in vivo studies have shown that D1 receptor activation stimulates adenylate cyclase and cyclic AMP (cAMP) production in endothelial cells (Bacic et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, we believe that DRD2 is expressed by cells of an immune origin -perhaps macrophages -and that these cells are probably responsible for inducing, in an autocrine and/or paracrine fashion, a decreased expression of VEGF when activated by DRD2-A. In this context, previous work by our group (Ferrero et al 2010) and other authors (Cristina et al 2005) has shown that cell populations expressing DRD2 (granulosa or pituitary cells) inhibit the secretion of VEGF in either an autocrine or a paracrine fashion. In this regard, it is known that most immune cell subtypes express DRD2 (McKenna et al 2002), and among them, macrophages are known to express large amounts of VEGF (Nap et al 2004).…”
Section: Discussionmentioning
confidence: 73%